Sociological Dimensions of Bilingual Communication in Yoruba and English in a Cosmopolitan City: A Case Study of Ibadanland - Adegbite, Wale (2014)
Several psychosocial factors influence the choice of Yoruba and English codes by indigenes of the cosmopolitan city of Ibadan for communication in various domains. This paper highlights some of these factors after describing some instances of code choice in the domains of education, family interaction, social interaction and official communication. The study reveals that apart from the general trend of preference for the choice of English for communication in official and public domains, some Ibadan indigenes are also beginning to use English more than Yoruba in informal domains. The over-utilization of English to the detriment of Yoruba, especially in public communication in the city, cannot but have some negative effects on social development. The paper therefore proffers recommendations related to efficient bilingual communication in Yoruba and English in Ibadan.